병원 노동쟁의의 쟁점과 그 결과분석 - 이준규 (연세대학교 보건대학원, 1990)
[한글] 이 연구는 병원노조 설립이후 각 병원에서 발생한 노동쟁의를 중심으로 쟁의의 원인이 되었던 주요쟁점과 결과를 분석함으로써 앞으로 원할한 노사관계 정립은 물론 병원노사문제 해결의 기초적 자료를 제공하는데 있다. 연구대상은 1987년 6월부터 1990년 5월말까지 쟁의가 발생한 병원을 대상으로 하였다. 그 결과는 다음과 같다. 1. 병원 노동조합 설립은 87년이전에는 5개에 불과했으나 87년 6.29선언이후 폭발적으로 증가하여 87년말에는 60개가, 88년말에는 160개, 그리고 90년 5월 현재 전국 562개 병원중 210개 군데에서 노조가 결성 되었다. 2. 병원 노동쟁의의 발생은 89년 상반기가 가장 많았으며, 그 다음으로 87년도 하반기, 88년 상반기등의 순으로 나타났다. 3. 병원 노동쟁의의 발생원인은 87년 6.29선언 및 신업화등에 따른 정치, 사회적인 외적요인과 다양한 직종으로 구성된 병원조직의 구조적인 문제등이 내적요인으로 작용했다. 4. 병원 노동쟁의의 유형은 산업체와 마찬가지로 사용자의 관리능력 부족과 노조의 지나친 요구와의 마찰로인한 쟁의 형태가 많았다. 5. 병원 노동쟁의의 특징은 초기에는 노사간의 감정적 대립과 상호불신으로 일어났으나 시간이 경과함에따라 노사양측이 과학적인 분석과 적극적이고 합리적으로 노사문제를 해결하는 양상을 보였다. 6. 병원 노동쟁의의 쟁점은 주로 경제적인 보상인 재정적인 지출을 요구하고 있었다. 이상의 결론을 토대로 바람직한 병원노사관계의 정립을 위해서는 성실한 타협과 교섭을 통해 해결하는 화해의 자세와 함께 분규를 사전에 예방할 수 있는 제도적 뒷받침이 절실히 요구된다. 할 수 있는 제도적 뒷받침이 절실히 요구된다. [영문] The purpose of this study is to set up a good relation between labor-management and supply some basic data for resolving the problems between labor and management by analytically studlying on some major points of dispute results from dispute with reference to labor disputes happened in various hospitals since the establishment of the labor union. The subjects of this study are hospitals where a labor dispute had happened at least once from July, 1987 to May, 1990. The results are follows: 1. There were only 5 hospital labor unions established before 1987, however since the proclamation of July 29(6. 29), the number of unions has explosively increased to 60 unions around late 1987, then 160 atound late 1988, and at present, May, 1990, 210 Hospital Labor Unions among total 562 hospitals nationwide have been set up. 2. The occurrence of hospital strikes was mostly in the first half of 1989, then in the latter half of 1987, next in the first half of 1988 in order. 3. The causes of hospital strikes are the political and social factors influenced by the proclamation of 6.29 for the external cause and the structural problems related to the characteristics of hospital organizations for the internal cause. 4. The types of hospital strikes were mostly such ones of the insufficient management ability of hospital employers and the discord between Labor Unions and hospitals because of somehow immoderate requirements by Labor Unions. 5. The features of hospital labor disputes were in the emotional confrontation and distrust between labor and management at the beginning, however it appeared that such confrontation and distrust were being graually settled down rationallly by a scientific analysis method. 6. The most point in hospital labor dispute was the demand of financial disbursement mainly tort economic compensation. Based on the conclusions made so far, it is desperately required, to set up a good relation between labor and management, that a posture of coexistence and coproaperity both by labor and management and a certain institutional support to prevent dispute beforehand should be pursued.
보건학과/석사